Getting started with MongoDB and NoSQL (LiveLessons (Indianapolis, Ind.), 2019)
"This LiveLesson gives first-time MongoDB users what they need to become successful database developers. Caleb Curry starts by clearly defining what MongoDB is and when you should consider it over a relational database. Throughout the course, Curry shows best practices on how to use MongoDB properly and avoid common pitfalls. He covers structured versus unstructured data, setup and getting started, CRUD commands (create, read, update, delete), aggregation, data models, transactions, indexes, security and authentication, administration, storage engines, and more. After finishing this course, users can create and manage a MongoDB database for their own data-driven applications."--Resource description page